Elementary School Physical Education Teachers’ Understanding of Technology-Based Physical Education Learning Media - Myrza Akbari; Rahmati; Razali; Misran; Myrna Lestari (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This study aims to determine the level of knowledge of PE teachers regarding IT-based learning media, which includes (1) knowledge of visual media, (2) knowledge of audio-visuals, (3) knowledge of computer usage, and (4) knowledge of internet usage. This type of research is descriptive with a quantitative approach. The population in this study were 40 elementary school PE teachers in East Aceh Regency. The instrument used in this study was a knowledge test instrument containing multiple-choice test questions. Based on the results of data analysis, it can be concluded that; (1) 92% of teachers have high knowledge, 7.5% have moderate knowledge, and no teachers have low knowledge about visual media, (2) 80% of teachers have high knowledge, 20% have moderate knowledge, and no teachers have low knowledge about audio visuals, (3) 35% of teachers have high knowledge, 65% have moderate knowledge, and no teachers have low knowledge for computer usage skills, (4) 40% of teachers have high knowledge, 52.5% have moderate knowledge, and 7.5% of teachers have low knowledge for internet usage skills. These results it can be concluded that the category of knowledge of Physical Education teachers against the media IT- based learning in Elementary Schools Throughout East Aceh Regency, it is high.